Unsteady flow due to a disk executing non-torsional oscillation and a Newtonian fluid at infinity rotating about non-coaxial axes - Ersoy, H. Volkan (INDIAN ACAD SCIENCES, 2017)
This paper is concerned with the unsteady flow of a disk performing non-torsional oscillation in its own plane and a Newtonian fluid at infinity while they are initially rotating with the same angular velocity about non-coaxial axes. For a more general study, it is considered that the disk executes non-torsional oscillation along any desired direction in its own plane. An exact solution obtained for the velocity field is compared with a periodic solution presented in order to find the time when the periodic flow starts. A very good agreement is found between the two solutions in the periodic state. It is an interesting result that the x- and y-components of the force per unit area exerted by the fluid on the disk vary in almost opposite direction when the non-torsional oscillation takes place along the eccentricity direction. Further, the change in the y-component of the translational velocity becomes noticeable in this case.
Keywords: Newtonian fluid; oscillating disk; non-coaxial rotation; exact solution; periodic flow; POROUS DISK; MAGNETOHYDRODYNAMIC FLOW; Engineering